METHODS OF DIATOM TEST: REVIEW OF LITERATURES (Journal of Forensic Medicine & Toxicology, 2013)
Diatom test is utilized as an important tool for diagnosis and confirmation of drowning deaths, and also for deducing the possible site drowning. For extraction of diatoms from human tissues like lung, liver, kidney, brain and bone marrow, several methods like Acid Digestion Method, Soluene-350 Method, Enzymatic Method, Membrane Filter Method, Colloidal Silica Gradient Centrifugation Method, Dry Ash Method etc. are used. Even for one method of extraction, different modifications have been used by different workers. For the purpose of identification and comparison of diatoms both in human tissue sample and water sample, besides commonly practiced light microscopy, scanning electron microscopy (SEM) are environmental scanning electron microscopy (ESEM) are also used by different workers. In the future, newer methods of identification of diatom using Nuclear Magnetic Resonance and Inductively Coupled Plasma Hyphenated Technologies, Atomic Force Microscopy (AFM), Flourimetry, Automatic Diatom Identification and Classification (ADIAC) etc. may add great value to the utility and reliability of diatom test for diagnosis and confirmation of drowning related deaths. The present paper is an overview of all such methods.
Keywords: Drowning; Diagnosis; Diatom; Diatom test; Methods of extraction; Identification of Diatom